Health Related Quality of Life amongst Sewerage and Sanitary Workers of Karachi, Pakistan - Fatmi, Syed Ishtiaq Ahmed; Mansoori, Naveed; Mubeen, Syed Muhammad (Pakistan Journal of Medical Sciences, 2022)
Objectives: To find out the impact of occupational and socio-demographic factors on the health related quality of life of sewerage and sanitary workers in Karachi.Methods: A cross-sectional study was conducted during 2019. Four hundred workers were chosen from five districts of Karachi using a non-probability convenient sampling technique. An Urdu version of WHO BRIEF quality of life questionnaire was used to collect the data about workers general health status and quality of life. Descriptive analysis was done and Chi-square test was used for the association of socio-demographic factors and quality of life. Multiple regression model was used to predict QOL of all domains. P-value<0.05 was considered as statistically significant.Results: Out of 400 sanitary workers, 228 (57.0%) were sweepers and the rest 172 (43.0) were sewerage workers. The majority of the workers 321 (80.3%) were male and 246 (61.5%) were illiterate. The vast majority of the workers 386 (96.5%) were not immunized against typhoid, / hepatitis and tetanus. Ninety-one percent (91%) were not using any kind of safety gadgets while at work. Male workers, married workers of both sexes and those with some education had a little better quality of life than their counterparts. Sanitary employees likewise had a higher quality of life score than sewage workers (P-value<0.05).Conclusion: The majority of workers, particularly sewage workers, have a very poor quality of life. Along with very bad working circumstances, their standard of living is significantly below par. They were not given any safety equipment. They were handling untreated sewage/waste with their bare hands, and they have never received a typhoid/hepatitis /tetanus vaccine.doi: https://doi.org/10.12669/pjms.38.7.5697How to cite this:Fatmi SIA, Mansoori N, Mubeen SM. Health Related Quality of Life amongst Sewerage and Sanitary Workers of Karachi, Pakistan. Pak J Med Sci. 2022;38(7):1986-1991. doi: https://doi.org/10.12669/pjms.38.7.5697This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.